Multicentre observational study of outcomes after drainage of acute perianal abscess. Issue 8 (7th April 2016) - Pearce, L.; Newton, K.; Smith, S. R.; Barrow, P.; Smith, J.; Hancock, L.; Kirwan, C. C.; Hill, J.; ,
Abstract : Introduction: Management of perianal abscesses has remained largely unchanged for over 50 years. The evidence for postoperative wound packing is limited and may expose patients to painful procedures with no clinical benefit and at considerable increased cost. Methods: Patients were recruited in 15 UK centres between December 2013 and October 2014. Outcome measures included number of dressing (pack) changes, healing, recurrence, return to work/normal function, postoperative fistula in ano and health utility scores (EQ‐5D™). Pain was measured before, during and after dressing change on a visual analogue scale. Results: Some 141 patients were recruited (median age 39 (range 18–86) years). The mean number of dressing changes in the first 3 weeks was 13 (range 0–21), equating to an annual cost to the National Health Service of €6 453 360 in England alone per annum. Some 43·8 per cent of wounds were healed by 8 weeks after surgery and 86 per cent of patients had returned to normal function. Some 7·6 per cent of abscesses had recurred and 26·7 per cent of patients developed a fistula in ano by 6 months following surgery. Patients reported a twofold to threefold increase in pain scores during and after dressing changes. Conclusion: Recurrent abscess is rare and fistula occurs in one‐quarter of the patients. Packing is painful and costly. Abstract : Painful and expensive